Physiotherapy in Semmelweis University Geriatrics Clinic and Center for Nursing Sciences - Handulle Hajir (Magyar Gerontológia, 2025)
The increasing global population of older and very elderly individuals poses significant challenges to healthcare systems, particularly in delivering efficient and sustainable care.